2012
DOI: 10.1167/tvst.1.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Fibrin Glue Spray Systems for Ophthalmic Surgery

Abstract: The standardization of the spray system for the application of FG in ophthalmology will provide an economical method for delivering consistent healing results after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In the present report we demonstrated that unpassaged SVF cells isolated from human subjects by LipiVage, a minimally invasive clinically approved procedure that routinely provides a high yield of viable adipocytes (11), and processed in a closed system (Tissue Genesis Cell Isolation System) could be suspended in Tisseel fibrin sealant and delivered using a commercially available aerosol spray system (12) while retaining the ability to differentiate into vessel-like endothelial tubules and adipocytes.…”
Section: Discussionmentioning
confidence: 93%
“…In the present report we demonstrated that unpassaged SVF cells isolated from human subjects by LipiVage, a minimally invasive clinically approved procedure that routinely provides a high yield of viable adipocytes (11), and processed in a closed system (Tissue Genesis Cell Isolation System) could be suspended in Tisseel fibrin sealant and delivered using a commercially available aerosol spray system (12) while retaining the ability to differentiate into vessel-like endothelial tubules and adipocytes.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, the time needed for the FG to crosslink is strongly affected by the thrombin/fibrinogen concentration, which determines the setting time of the fibrin sealant, ranging from 30 s (rapid setting) to several minutes (slow setting). [ 28 ] The composition also affects the conversion of fibrinogen into fibrin clots, which form a mesh and an dense protofibril packing with a nanometer size, which probably impedes the entanglement of the GG polymeric chains (the average weight of the polymeric chains is 500 000 Da) upon FG assembly. This may hamper material penetration within the crosslinked solution over time.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, careful attention and precisely controlled placement are required during blow-out fracture surgery using fibrin glue. Even if the surgical field of view is narrow, we must visually check whether fibrin glue is applied properly to the desired area with a homogeneous thickness, and a spray applicator can help for this purpose [ 16 ]. After application, tissue traction should be maintained until clot formation.…”
Section: Discussionmentioning
confidence: 99%